2021
DOI: 10.1088/1742-6596/1753/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality technology as a tool to improve the efficiency of maintenance and analytics of the operation of electromechanical equipment

Abstract: Today the industry is facing a shortage of skilled workers and an aging workforce, which will eventually lead to a loss of knowledge. But augmented reality technology can connect field workers with experts who are able to provide remote guidance in real time. The subsequent advantage is that the information obtained by AR devices can be used as accumulated successful experience in the future, which facilitates decision-making in specific business processes of the company. With AR, employees gain experience and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Zhukovskiy et al [41] and Koteleva et al [42] developed augmented reality modules for performing electrical equipment maintenance. In both cases, the authors concluded that the use of the augmented reality system can reduce the cost of maintaining electrical equipment.…”
Section: Electrical Energy Systems Applicationsmentioning
confidence: 99%
“…Zhukovskiy et al [41] and Koteleva et al [42] developed augmented reality modules for performing electrical equipment maintenance. In both cases, the authors concluded that the use of the augmented reality system can reduce the cost of maintaining electrical equipment.…”
Section: Electrical Energy Systems Applicationsmentioning
confidence: 99%
“…The architecture of the control system of intelligent low-voltage switchgear (LVS) of electricity is as follows and a detailed description is presented in [49]. Data transfer is carried out according to the following scheme in Figure 1 (all figures in the research were compiled by the authors):…”
Section: Information Modelmentioning
confidence: 99%
“…Egger and Masood [21] described the recent spread of AR technologies and stated that these are not yet ready for industrial implementation in some areas, whereas they are in other sectors. The most common applications of AR concern training for the management of operations [22][23][24] and assisting in the routine maintenance of industrial equipment by following visual instructions and interactive guides superimposed on the real equipment for a more effective workflow, even with remote assistance [25][26][27][28][29]. Yang et al [30] described how AR, combined with instant messaging and image recognition technologies, could greatly assist chemical plant inspections to solve the problems associated with low efficiency and poor standardisation.…”
Section: Introductionmentioning
confidence: 99%